Three-dimensional imaging of cleared human liver tissues reveals extensive fibrosis heterogeneity in non-alcoholic fatty liver disease - Yiğit, Buket; Özgönül, Ekin; Yaman, Ömer; Ulukan, Burge; Çetin Taş, Yağmur; Morova, Berna; Aydın, Musa; Uysallı, Yiğit; Demirtaş, Elif; Erkan, Mert; Gürsoy Özdemir, Yasemin; Karahüseyinoğlu, Serçin; et al. (Elsevier, 2022)
Background and aims: Liver fibrosis is a dynamic process of fibrogenesis and fibrolysis traditionally evaluated by liver biopsy. Accurate assessment of hepatic fibrosis is vital for optimal biomarker and drug development in the era of NASH clinical trials. The limitations of biopsy-based fibrosis staging include semi-quantitative assessment, sampling, and observer variability. In this study, we aimed to perform 3D imaging of optically transparent whole liver biopsy samples by light sheet fluorescence microscopy (LSFM) to quantify extra-cellular matrix proteins.
Keywords: Liver Tissues; Fibrosis Heterogeneity; Fatty Liver Disease